We will learn how to prove the property of the inverse trigonometric function 3 arcsin(x) = arcsin(3x - 4x\(^{3}\)) or, 3 sin\(^{-1}\) x = sin\(^{-1}\) (3x - 4x\(^{3}\))
Proof:
Let, sin\(^{-1}\) x = θ
Therefore, sin θ = x
Now we know that, sin 3θ = 3 sin θ - 4 sin\(^{3}\) θ
⇒ sin 3θ = 3x - 4x\(^{3}\)
Therefore, 3θ = sin\(^{-1}\) (3x - 4x\(^{3}\))
⇒ 3 sin\(^{-1}\) x = sin\(^{-1}\) (3x - 4x\(^{3}\))
or, 3 arcsin(x) = arcsin(3x - 4x\(^{3}\)) Proved
● Inverse Trigonometric Functions
11 and 12 Grade Math
From 3 arcsin(x) to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Apr 15, 24 01:29 AM
Apr 15, 24 01:13 AM
Apr 14, 24 03:06 PM
Apr 14, 24 02:23 PM
Apr 14, 24 02:01 PM